THE POLITENESS OF TOUR GUIDES TO EXPLAIN TOURIST DESTINATION TO TOURISTS IN PURA MANGKUNEGARAN SURAKARTA (FOCUSED ON SPEECH ACT) - KHOTIMAH, ARUM WULAN NURUL; ALI, SOPYAN (RADIANT: Journal of Applied, Social, and Education Studies, 2020)
Indonesia is a tourist destination in the world that amaze the beautiful Nation. Indonesia has nature and historical tourist attraction. Many historical tourist attraction are found in central java especially in Solo. Solo has Surakarta palace, Pura Mangkunegaran, Radya pustaka museum, Monumen pers, Sangiran museum, etc. The writer interests to do research about "the politeness of tour guides to explain tourist destination to tourists in Pura Mangkunegaran Surakarta (focused on speech act). The method is used are quantitative and qualitative. In this research needs to use the qualitative method because the data source of the research are units language, the level of words, phrases, clauses, and sentences. The relevant context and cultural value. The data source of the research is descriptive text. Descriptive research explains the reality of the data that appear, analyzed in narrative form. Tour guide has to understand material and be capable explaining to tourists clearly. Usually there is job training to tour guide first. After trainer gives permission, then tour guide ready to do their job. Tour guide makes a note for daily activity as tour guide in Pura Mangkunegaran Surakarta. Then tour guide can take a rest and prepare to do their job again after that. There are activities of tour guide in Pura Mangkunegaran Surakarta that can be seen by the writer.